LEGAL REGULATION OF PUBLIC SAFETY IN RAILWAY TRANSPORT IN UZBEKISTAN - Alikhonov Bekhzod Nizamidinovich (Modern American Journals, 2026)
The article analyzes the legal foundations of administrative and legal regulation of ensuring public safety in railway transport. The study examines normative legal acts in the field of transport safety, state and international legal norms, as well as the powers and responsibilities of transport entities. The article scientifically considers the legal mechanisms for ensuring safety in railway transport, administrative and organizational measures, and practical measures.
Keywords: Railway transport, public safety, transport safety, administrative and legal regulation, normative legal acts, legal mechanism.